It is still too early to promote biodegradable mulch film on a large scale: A bibliometric analysis - Liu, Liyuan; Zou, Guoyuan; Zuo, Qiang; Li, Shunjiang; Bao, Zhe; Jin, Tuo; Liu, Dongsheng; Du, Lianfeng (Environmental technology & innovation, 2022)
Biodegradable mulch film was considered to be a sustainable ecological alternative alleviate of plastic mulch film. Extensive studies related to biodegradable mulch film have been carried out in multiple perspectives. However, there was no systematic synthesis of the studies because of the complex research subjects, diverse research contents, and plentiful research perspectives in this field. In the present study, a bibliometric analysis was applied to analyze the evolution and current status of the research about biodegradable mulch film, so as to reveal research hotspots and predict future trends. The research about biodegradable mulch film had developed from a field concentrated on material development to multi-disciplinary field with three main research knowledge bases: the necessity of degradable mulch film application, mulching on crop production and degradation process of biodegradable mulch film. The study hotspot has shift from development of biodegradable materials to farmland application of the biodegradable mulch film. The ecotoxic of degradation process and degradation products especially for microplastics of biodegradable mulch film on soil environment was getting the attention of scientists. Based on these findings and status quo, three research directions including development of renewable biodegradable materials with higher water resistance performance, farmland suitability evaluation of biodegradable mulch film and safety evaluation of farmland soil with biodegradable film mulching. It is still too early to apply biodegradable mulch film on a large scale because its potential ecotoxicity to soil environments is not identified yet. [Display omitted] •Biodegradable mulch film has developed to multi-disciplinary field.•Environmental effect assessment will be future hotspot for biodegradable mulch film.•It is still too early to apply biodegradable mulch film on a large scale.